Building Bridges and Strengthening Bonds: Exploring the Impact of Community Engagement on Enhancing Police-Community Relationships - Blanco, Kimberly (Technium Social Sciences Journal, 2025)
Community engagement initiatives have become essential in fostering positive relationships between the police and local communities. This study aims to know the effects and impacts of such initiatives on enhancing police-community relationships in Baguio City and to identify the factors that contribute to the effectiveness of these engagement strategies. Understanding these elements is crucial for developing sustainable approaches to community policing and improving public safety. Using a qualitative descriptive research design, in-depth interviews were conducted with 15 participants, including police officers, community members, and barangay officials. Thematic analysis was employed to explore participants’ experiences and perspectives regarding community engagement practices and their influence on trust, cooperation, and mutual understanding between police and residents. Findings reveal that community engagement initiatives significantly build and reinforce trust, improve perceptions of safety, and facilitate positive police-community interactions. Key factors contributing to the effectiveness of these strategies include clear objectives, well-designed programs, active community involvement, collaborative partnerships with NGOs, and robust support from local government. Additionally, continuous feedback mechanisms and resource management were found essential for sustaining these initiatives. This study contributes valuable insights to the existing literature by highlighting the critical role of strategic planning and community collaboration in strengthening police-community relations. Practically, the findings underscore the importance of sustained, inclusive, and well-supported engagement efforts to foster long-term trust and cooperation, providing a model for similar urban communities seeking to enhance public safety and social cohesion.